Her ebook A novel. - Lane, Harriet (2015)
You don't remember her — but she remembers you. Two different women; two different worlds. On the face of it, Emma and Nina have very little in common. Isolated and exhausted by early motherhood, Emma finds her confidence is fading fast. Nina is sophisticated and assured, a successful artist who seems to have it all under control. And yet, when the two women meet, they are irresistibly drawn to each other. As the friendship develops, as Emma gratefully invites Nina into her life, it emerges that someone is playing games-and the stakes could not be higher. What, exactly, does Nina see in Emma? What does she want? And how far will she go in pursuit of it? A gripping novel about friendship and identity, about the wild hopes and worst fears of parenthood, about the small and easily forgotten moments that come to define a life, Her is unputdownable-compelling and hauntingly discomfiting.